Antiproliferative Activity of Fucan Nanogel - Francisco Miguel Gama; Hugo Alexandre Oliveira Rocha; Paula Pereira; Silvia Santos Pedrosa; Arthur Anthunes Jacome Vidal; Ruth Medeiros Oliveira; Dayanne Lopes Gomes; Jailma Almeida-Lima; Nednaldo Dantas-Santos (Marine Drugs, 2012)
Sulfated fucans comprise families of polydisperse natural polysaccharides based on sulfated l-fucose. Our aim was to investigate whether fucan nanogel induces cell-specific responses. To that end, a non toxic fucan extracted from Spatoglossum schröederi was chemically modified by grafting hexadecylamine to the polymer hydrophilic backbone. The resulting modified material (SNFuc) formed nanosized particles. The degree of substitution with hydrophobic chains was close to 100%, as estimated by elemental analysis. SNFfuc in aqueous media had a mean diameter of 123 nm and zeta potential of −38.3 ± 0.74 mV, as measured by dynamic light scattering. Nanoparticles conserved their size for up to 70 days. SNFuc cytotoxicity was determined using the MTT assay after culturing different cell lines for 24 h. Tumor-cell (HepG2, 786, H-S5) proliferation was inhibited by 2.0%–43.7% at nanogel concentrations of 0.05–0.5 mg/mL and rabbit aorta endothelial cells (RAEC) non-tumor cell line proliferation displayed inhibition of 8.0%–22.0%. On the other hand, nanogel improved Chinese hamster ovary (CHO) and monocyte macrophage cell (RAW) non-tumor cell line proliferation in the same concentration range. The antiproliferative effect against tumor cells was also confirmed using the BrdU test. Flow cytometric analysis revealed that the fucan nanogel inhibited 786 cell proliferation through caspase and caspase-independent mechanisms. In addition, SNFuc blocks 786 cell passages in the S and G2-M phases of the cell cycle.